Creating a Mobile App to Teach Ethical Social Media Practices. - Cooner, Tarsem Singh; Knowles, Alan; Stout, Brian (Social Work Education, 2016)
Social media has transformed the way individuals and communities interact. The number of mobile devices connected to social media networks has increased exponentially over the last few years. These devices tend never to leave the sides of their owners and offer potentially limitless flexible opportunities for communication and learning. This article initially outlines how an individual social work academic created a mobile phone and tablet app to help students explore the ethical uses of social media in social work. The aim was to encourage discussion around the theoretical and technical challenges posed when seeking to ensure an educational mobile app was grounded in social work as opposed to Information and Communication Technology principles of learning. Students’ experiences of using the app in Australia, Canada and the UK are analysed. The evaluation suggests that the scenario-based principles underpinning the design and engaging in learning on the mobile platform had both positive and negative impacts on student learning. The article details the lessons learned from these processes.